Evaluation of the COVID-19 Handling Programs and National Economic Recovery in Indonesia - Kennedy, Posma Sariguna Johnson (Fundamental Management Journal, 2021)
This study aims to see the budget allocation for the Covid-19 Handling Program and National Economic Recovery (PC-PEN), based on realizing the PC-PEN Program budget in 2020 and the challenges in 2021. The research method in this study is to use a qualitative approach through a review of the literature with the primary source coming from the Ministry of Finance, especially from the Warta Fiskal published by the Fiscal Policy Agency of the Ministry of Finance of the Republic of Indonesia, as well as other supporting sources. From data through literature, social protection programs and support for Micro, Small, and Medium Enterprises (UMKM) show significant budget absorption development. While the health management program, sectoral support from ministries/agencies and local governments, and business incentives, the absorption is still low. The Government must pay attention to the implementation and effectiveness of the PC-PEN Program, including maintaining the most subordinate economic groups' consumption and giving priority to the distribution of stimulus funds to the sectors most affected by this pandemic. Keywords: Pandemic Covid-19, National Economic Recovery (PEN), PEN Budget